Cu catalyzed [4 + 2] cycloaddition for the synthesis of highly substituted 3-fluoropyridines. Issue 18 (25th April 2022) - Fu, Yiwei; Shi, Haoyu; Lei, Shengshu; Shi, Lei; Li, Hao
Abstract : A copper catalyzed [4 + 2]annulation–aromatization of benzyl trifluoromethyl ketimines with 3-acryloyloxazolidin-2-ones has been developed for the synthesis of 3-fluoropyridines in moderate yields through double C–F bond cleavages. Abstract : A copper catalyzed annulation–aromatization of benzyl trifluoromethyl ketimines with 3-acryloyloxazolidin-2-ones for the synthesis of 3-fluoropyridines through double C–F bond cleavages has been developed. In this approach, the annulation occurred between the in situ formed dienes from trifluoromethyl ketimines via the first C-F bond cleavage and 3-acryloyloxazolidin-2-ones. Then the aromatization afforded 3-fluoropyridines in moderate yields through the second C–F bond cleavage. The 3-fluoropyridine products could be further hydrolyzed to multi-substituted 3-pyridinecarboxylic acids.